AN ANALYSIS OF SLANG IN THE GOLDEN CIRCLE IN THE KINGSMAN MOVIE (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this study were to determine the type and function of the slang used in kingsman movie: the golden circle. The data source was taken from the script kingsman movie: the golden circle. The research design used in this research was descriptive qualitative research. There were five words of slang and eight words function of slang. Then the slang word in the form of words were classified and analyzed. These findings revealed that there were 13 slang words and function in kingsman movie: the golden circle that had been classified into a type of slang and function of slang.